2021
DOI: 10.1002/anie.202110455
|View full text |Cite
|
Sign up to set email alerts
|

A Click Chemistry Approach to Targeted DNA Crosslinking with cis‐Platinum(II)‐Modified Triplex‐Forming Oligonucleotides

Abstract: Limitations of clinical platinum(II) therapeutics include systemic toxicity and inherent resistance.M odern approaches,t herefore,s eek new ways to deliver active platinum(II) to discrete nucleic acid targets.I nt he field of antigene therapy, triplex-forming oligonucleotides (TFOs) have attracted interest for their ability to specifically recognise extended duplex DNAtargets.Here,wereport aclickchemistry based approach that combines alkyne-modified TFOs with azide-bearing cis-platinum(II) complexes-based on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 46 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…An internally modified 31 nucleotide poly-pyrimidine parallel-binding TFO was produced by solid-phase synthesis in a similar manner to earlier reported TPMA-TFOs. ( 35 ) This TFO was selected as previous studies have reported thermal stability > 37°C ( 35 , 38 ) and increased target discrimination for internally modified AMN-TFO hybrids. ( 35 )…”
Section: Methodsmentioning
confidence: 99%
“…An internally modified 31 nucleotide poly-pyrimidine parallel-binding TFO was produced by solid-phase synthesis in a similar manner to earlier reported TPMA-TFOs. ( 35 ) This TFO was selected as previous studies have reported thermal stability > 37°C ( 35 , 38 ) and increased target discrimination for internally modified AMN-TFO hybrids. ( 35 )…”
Section: Methodsmentioning
confidence: 99%
“…Two TFO motifs are possible: pyrimidine-rich TFOs bind in a parallel manner, while purine-rich TFOs bind in an anti-parallel orientation. The pyrimidine-rich TFOs consisting primarily of thymines (T) or protonated cytosines (C + ) bind to DNA with AT and GC base pairs to form the canonical base triads T:AT and C + :GC with duplex DNA ( Beal and Dervan, 1991 ; Hennessy et al, 2022 ). Typically, pyrimidine-rich TFOs can only form the triple-helix formation under acidic conditions.…”
Section: Characteristics Of Triplex-forming Oligonucleotidesmentioning
confidence: 99%
“…A similar approach was recently reported in the context of (non-luminescent) cis -Pt(II)-modified triplex-forming oligonucleotides. 36 …”
Section: Introductionmentioning
confidence: 99%